De las culturas juveniles a las ciberculturas del siglo XXI - Muñoz González, Germán (2023)
The understanding of youth cultures requires a socio-historical reading of its genesis and evolution. It could be considered that youth cultures of the twentieth century have their roots in the catastrophic event called “World War II”, and in this context, they construct their proposal and resistance. The autor advocates a new event that generates youth cyber-cultures in the XXI century: the emergence of a media-related global culture. Retaining common elements, the result is the production of new subjectivities and worlds of adolescent life. What mutations are drawn and how are they affecting the subjects of education?